Romantic jealousy: a test of social cognitive and evolutionary models in a population-representative sample of adults - Visser, R.; Richters, J.; Rissel, C.; Grulich, A.; Simpson, J.; Rodrigues, D. L.; Lopes, D. (Journal of Sex Research, 2020)
Whereas sexually dimorphic evolutionary models argue for clear sex differences in responses to jealousy-evoking scenarios, social cognitive models emphasize the importance of other factors. This paper explores variables associated with responses to a commonly-used jealousy-evoking scenario in a population-representative sample. Data from 8,386 Australian men and women aged 16–69 were weighted to match the population. The results provided some support for evolutionary models among heterosexual respondents, but findings contrary to evolutionary models were found among non-heterosexual respondents. Support for social cognitive models was provided by the identification of six variables that had significant independent multivariate associations with jealousy: sex, age, education, lifetime number of partners, relationship status, and attitudes toward infidelity. The results suggest that although men and women may tend to respond differently to sexual or emotional infidelity scenarios, the anticipated experience of jealousy in each context is strongly influenced by biographical and cultural factors.